Maternal mortality : report of meeting held at Friends' House. Euston Road on November 15, 1932 (London : Maternal Mortality Committee)
1932-11 1932 1930s 36 pages Midwives deal with normal cases and anaesthetics do not come into their province, but they are concerned with the use of analgesics and those homely sedatives which we who watch by the mother hour after hour know very well are enormously helpful, and we as midwives ask that we may be better taught how to use those alleviations that mothers need. Now these alleviations are no use, as all workers know, for the moment of birth, and until lately only our well-to-do mothers have been able to have the benefit of what is called chloroform à la Reine, because Queen Victoria was so thankful to have it when her children were born, that is to say, a drop or two of chloroform at a time which deadens the pain but does not make the mother insensible. Now it has been discovered that it is possible to put up this precious drug in such tiny quantities that they are perfectly safe, in crushable glass capsules, and it is not anaesthesia but analgesia that these produce. It deadens the pain for the mother, and experiments are now taking place in seventy hospitals, thanks to the beneficence of the National Birthday Trust Fund. If the experiments are as successful as the first reports foreshadow, midwives ask to be allowed to use these crushable capsules so that the 60 per cent. of the mothers that they have to deal with may have this relief. We shall then perhaps hear less of the impatience of which the Minister spoke. There is another aspect of the question and that is the relief of the mother from the fear of pain. There is much unnecessary distress during the course of labour because of the mother's fear of the last pains. Now everybody knows that fear has a very lowering effect upon the system, and it does not seem to us (though we are not trained in science as much as we should like to be) at all impossible that a mother who is tired with a long labour in which sedatives have not been given, and frightened of what is to come, would provide an organism much more likely to succumb to any germ of sepsis that might be about than if she had had proper relief during her labour and no fear. In this way we think that fear may contribute to the question of maternal deaths. We are very glad that the Reports stress the safety of the home and the normal aspect of childbirth because pregnancy and childbirth after all are homely functions, and midwives are the proper attendants. They are the friends of the mother, freely chosen by her as confidant and helper. We need, of course, much more knowledge and skill in ante-natal care. I have just come this morning from Holland, where I had the opportunity of talking with the Midwife Superintendent of their Midwives' Training School, and I said to her : "To what do you attribute Holland's wonderfully low maternal mortality rate?" and she said : "To our ante-natal teaching and the carrying of it out." (16) 292/824/1/45